2012
DOI: 10.3109/08958378.2012.724728
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of e-cigarette vapor and cigarette smoke on indoor air quality

Abstract: For all byproducts measured, electronic cigarettes produce very small exposures relative to tobacco cigarettes. The study indicates no apparent risk to human health from e-cigarette emissions based on the compounds analyzed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
196
1
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 272 publications
(221 citation statements)
references
References 13 publications
16
196
1
5
Order By: Relevance
“…Since e-cigarettes heat rather than burn, the production of toxins and carcinogens is far lower than from conventional tobacco smoking [1][2][3]. Following introduction into Europe and the US in 2006, e-cigarette use has become increasingly popular with sales in the US doubling each year from $20m in 2008 to $750m -$1bn in 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Since e-cigarettes heat rather than burn, the production of toxins and carcinogens is far lower than from conventional tobacco smoking [1][2][3]. Following introduction into Europe and the US in 2006, e-cigarette use has become increasingly popular with sales in the US doubling each year from $20m in 2008 to $750m -$1bn in 2013.…”
Section: Introductionmentioning
confidence: 99%
“…2,3,4 Unlike cigarettes, e-cigarettes do not produce side-stream smoke, 5 and exposure studies suggest that they do not contain the same levels of harmful chemicals that cigarettes do. 2,4,5,6 However, the vapours…”
Section: Introductionmentioning
confidence: 99%
“…Since exposure to toxins from smoking conventional cigarettes is primarily the result of the combustion process, substituting cigarettes with noncombusted products such as smokeless tobacco or e-cigarettes could theoretically reduce the adverse health consequences caused by cigarette smoking among those who would not have quit tobacco entirely (Levy et al, 2004(Levy et al, , 2006Royal College of Physicians, 2007). For example, it has been demonstrated that e-cigarette vapor contains lower levels of carcinogens and toxicants than cigarette smoke (Goniewicz et al, 2013;McAuley, Hopke, & Zhao, 2012), which could theoretically reduce smoking-related disease rates if cigarette smokers who would not otherwise quit would completely switch to e-cigarettes. On the other hand, the Institute of Medicine (IOM) warns that availability of other tobacco products may have a net negative impact on public health since smokers might delay or refrain from quitting, former smokers may be drawn back to tobacco use, and nonsmokers might be encouraged to start using tobacco (IOM, 2012).…”
Section: Introductionmentioning
confidence: 99%